2005
DOI: 10.1109/tdei.2005.1453458
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the performance of flat-surface, high-gradient vacuum insulators

Abstract: High-gradient insulators HGI are periodic assemblies of conducting and insulating layers that have been shown to withstand higher pulsed voltages in vacuum than homogeneous insulators of the same length. We carried out calculations and experimental studies to understand the effect of geometry on the performance of wellconditioned, flat-surface HGI assemblies. We tested stacks with several different ( values of Ir r r r rM where I is the axial length of an insulating layer and M is the length ) of a metal layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…The best alumina structure tested by Leopold did not exceed the breakdown strength of conventional structures until after 2500 conditioning pulses 18 , which may be partly due to a slower conditioning process than was seen by us. In fact, the conditioning procedures used by us may be too aggressive.…”
Section: A Testing Procedures and Conditioningmentioning
confidence: 45%
See 2 more Smart Citations
“…The best alumina structure tested by Leopold did not exceed the breakdown strength of conventional structures until after 2500 conditioning pulses 18 , which may be partly due to a slower conditioning process than was seen by us. In fact, the conditioning procedures used by us may be too aggressive.…”
Section: A Testing Procedures and Conditioningmentioning
confidence: 45%
“…Conditioning was observed by Elizondo in structures formed from Lexan interleaved with thin stainless steel sheets 17 , and by Leopold in structures formed from alumina and thick Kovar rings 18 . Conditioning was not observed by Sampayan in structures formed from silica with sputtered gold electrodes 19 .…”
Section: A Testing Procedures and Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…This will require either an HGI sample and more highly polished and/or greened electrodes, or construction of a higher voltage test stand. The conclusions drawn by Leopold, et.al [2] indicate a more optimal spacing of the conductors. We plan to investigate this mechanism further by fabricating and testing high gradient insulators with alternate conductor intervals under pulsed and DC conditions.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the HGI appears to behave as an ensemble of independent insulator structures [1] as shown in figure 1. Figure 1 Recent research at other laboratories both in the US and abroad have suggested that the improved performance of this topology is resultant from an alternating gradient formed by the multiple metal/dielectric intervals along the insulator surface [2]. This theory suggests electrons are deflected away from the insulator as a result of the alternating gradient thus inhibiting the production of secondary electrons leading to a cascade failure and insulator flashover.…”
Section: Introductionmentioning
confidence: 99%